Opolskie Voivodship “Gazelle” Innovation Potential - Aleksandra Zygmunt; Mirosława Szewczyk (Barometr Regionalny)
The necessity for enterprises to adapt to constantly changing surrounding requires innovation activities, which impact regional development. In that area the essential meaning for a particular region’s innovation potential is driven by enterprises, which are characterized by more than proportional growth. The conducted studies are based on the assumption that the fundamental role in a region is played by enterprises which very rapidly increase in value — known as “gazelles.” The main purposes of the study is the examination of gazelles in Opolskie Voivodship. The paper consists of two parts. The first part contains considerations of issues connected with innovations of regions, their innovation potential and the significance of gazelles in improving the level of a region’s innovations. The second part is concentrated on the analysis of gazelles in Opolskie Voivodship. Analysis was made of the activities structure of Opolskie Voivodship’s gazelles, their segmentation based on technological intensity (manufacturing) and knowledge-intensive activities (services). The research also contains a structure similarity comparison. The essential data source used was Forbes’ rating “Forbes Diamonds.” The period under analysis is 2009–2013.